Plunkett's advertising & branding industry almanac 2021 : the only comprehensive guide to advertising companies & trends - Plunkett, Jack W.; Plunkett Research, Ltd. (Houston, Texas (P.O. Drawer 541737, Houston TX 77254-1737 USA) : Plunkett Research, Ltd., 2021)
The data and areas of interest covered are intentionally broad, ranging from branding trends to emerging technologies, to an in-depth look at the major firms within the many segments that make up the advertising and branding industry.
1. Major trends affecting the advertising & branding industry -- 2. Advertising & branding industry statistics -- 3. Important advertising & branding industry contacts -- 4. The Advertising 300: who they are and how they were chosen.
Includes glossary and indexes.
Also available in print.
Mode of access: World Wide Web.
Title from PDF title page (viewed on May 27, 2021).
Keywords: Advertising -- Directories; Advertising -- Statistics; Marketing -- Directories; Marketing -- Statistics